The Effectiveness of Summarizing Strategy to Improve Senior High School Students’ Reading Comprehension - Aisya Rafida Salma (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to determine the effectiveness of the summarizing strategy in improving reading comprehension of 10th grade high school students. The background of this study is based on the low ability of students to understand English reading, especially in identifying main ideas and compiling summaries. This study uses a quantitative method with a quasi-experimental design, involving two classes as the experimental and control groups. The instruments used are multiple-choice pretests and posttests that measure students' reading comprehension. The results of the analysis showed that there was a significant increase in the posttest scores of students in the experimental group compared to the control group. The independent sample t-test produced a significance value (p = 0.001), and the effect size calculation showed an eta square value of 0.40 (large effect). These findings indicate that the summarizing strategy is effective in improving students' reading comprehension at the high school level.